Ethical Considerations in the Age of Artificial Intelligence: Balancing Innovation and Social Values - Rochmi Hastuti; Syafruddin (Westscience Press, 2023)
This research presents a comprehensive analysis of the ethical considerations in the age of artificial intelligence (AI) through bibliometric exploration and VOSviewer visualizations. The study systematically reviews scholarly literature to uncover prevailing themes, influential works, key authors, and emerging trends within AI ethics. The co-authorship analysis identifies collaborative networks, emphasizing interdisciplinary engagement in addressing ethical challenges. Keyword co-occurrence analysis highlights core themes, including big data, social value, algorithm, and ethical aspect, underscoring the multifaceted nature of AI ethics. Citation analysis reveals seminal works that have significantly shaped the discourse. The findings offer insights into the dynamic evolution of AI ethics, where diverse considerations intersect, from technology's societal impact to stakeholder management. The study's implications extend to researchers, policymakers, and practitioners, guiding responsible AI development aligned with human values.